Learning Factories in Practice: The Example and Development Proposal of Mini Company Located in the Automotive Science Park Based on International Best Practices - Dániel Szabó; Fanni Csikós; Viktória Panker; Izabella Kovács (Engineering Proceedings)
The focus of this study is on presenting the concept of the Mini Company initiative launched in 2023 in the ZalaZONE automotive science park and proposing its development through international good examples. The aim of the project, based on the learning factory model, is to enable dual university students to experience the real market environment in a realistic, educational environment. The search for international good examples can help to further develop the concept, especially regarding the future role of automotive stakeholders. The presented results and good examples can be used in new research projects, develop teaching methods, and strengthen cooperation between industry and academia.